|x^2 - 6x + 1| = x^2 - 9
Раскроем модуль, получим 2 системы:
1) x^2-6x+1≥0
x^2-6x+1=x^2-9
2) x^2-6x+1<0
-(x^2-6x+1)=x^2 -9
(1) x^2-6x+1≥0 ⇔ x∈ (-∞; 3-√8] ⋃[3+√8; +∞)
D=36-4=32
√D=√32 =2√8
x1=(6+2√8)/2 = 3+√8 ≈ 5,8
x2=(6-2√8)/2 = 3-√8 ≈ 0,17
x=5/3 = 1, (6) ⇒не входит в x∈ (-∞; 3-√8] ⋃[3+√8; +∞)
2) x^2-6x+1<0 ⇔ x∈(3-√8; 3+√8)
D=36-4=32
√D=√32 =2√8
x1=(6+2√8)/2 = 3+√8 ≈ 5,8
x2=(6-2√8)/2 = 3-√8 ≈ 0,17
-(x^2-6x+1)=x^2 -9
-x^2+6x-1-x^2+9=0
x^2-3x-4=0
D=9+16=25=5^2
x1=(3+5)/2 = 8/2 = 4⇒∈ (3-√8; 3+√8)
x2=(3-5)/2 = -2/2 = -1⇒∉ (3-√8; 3+√8)
x=4
4х²-19х+32+6х²+6х-41=0
10х²-13х-9=0
D=169-4*10*(-9)=529
x1=(13+23)/20=36/20=1.8
x2=(13-23)/20=-1/2=-0.5